2018
DOI: 10.1590/1413-81232018232.02862016
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and factors associated with hypertriglyceridemic waist in the elderly: a population-based study

Abstract: Prevalence and factors associated with hypertriglyceridemic waist in the elderly: a population-based study Prevalência e fatores associados à cintura hipertrigliceridêmica em idosos: um estudo de base populacional

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
1
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
2
1
2
2
Order By: Relevance
“…HTGW + prevalence was elevated in our population. Factors such as age, BMI, tobacco use, adherence to the MedDiet, and total energy expenditure were associated with the presence of HTGW, in accordance with Fagundes et al . In this study, the population aged ≥ 60 years had a high prevalence of HTGW, with physical inactivity and overweight as key factors associated with this phenotype.…”
Section: Discussionsupporting
confidence: 89%
“…HTGW + prevalence was elevated in our population. Factors such as age, BMI, tobacco use, adherence to the MedDiet, and total energy expenditure were associated with the presence of HTGW, in accordance with Fagundes et al . In this study, the population aged ≥ 60 years had a high prevalence of HTGW, with physical inactivity and overweight as key factors associated with this phenotype.…”
Section: Discussionsupporting
confidence: 89%
“…The strongly positive association between HTGW with the female sex, age, body mass index and high blood glucose levels, agree with that found in Brazilian older adults (24,32)This association makes clear the importance of anthropometric indicators as indirect evidence of metabolic disorders, since it has been shown that the increase in body volume provides an environment conducive to the development of metabolic disorders especially in women, after the menopause, period in which women reduce their levels of physical activity, increase their social stress and adopt inappropriate nutritional styles, which ultimately leads to an increase in body weight (35). The inverse association between smoking and HTGW is surprising in our study, although it has been reported that the cessation of smoking is linked to the increase in body weight and adiposity indexes (36).…”
Section: Discussionsupporting
confidence: 89%
“…In this study, we found that the prevalence of HTGW among the older adults in Colombia is higher in men than in women and there were significant differences in terms of sex and possible risk factors. In the present study, the prevalence of HTGW in the older adults was 38.7%, a percentage that is much higher than that reported in Brazilian older adults (27.1%) (24) and Chinese (23.71%) (25). In this and other studies (9,24,26), women have the highest prevalence of HTGW, a result that is alarming since this phenotype ends up completing the ominous picture of metabolic syndrome in older adults women, in addition to the increase in body weight.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…24−26 A prevalência de indivíduos com FCH neste estudo foi maior dentre o sexo masculino. Apesar de este resultado diferir do encontrado em estudos nacionais, [27][28][29] Quando se tem valores aumentados de PC, como no caso do FCH, há um aumento na gordura abdominal e visceral, que leva a um aumento também da atividade lipolítica nos adipócitos e por causa disso maior liberação de ácidos graxos livres que se acumulam nas células principalmente do fígado, músculos e pâncreas. O excedente de ácidos graxos no fígado servirá como substrato para a produção de triacilgliceróis hepáticos e lipoproteínas ricas em triacilgliceróis na circulação.…”
Section: Discussionunclassified